Vitritis and retinal vasculitis caused by pseudorabies virus - Manman Ying (SAGE Publishing, 2021)
Pseudorabies virus (PRV) is a herpesvirus of swine. PRV is also called suid herpesvirus 1 and is a member of the Alphaherpesvirinae subfamily within the family Herpesviridae. The number of PRV cases worldwide is small, but in susceptible individuals, infection with this virus has a poor prognosis. Therefore, it is urgent to improve our understanding of this disease in clinical practice to avoid misdiagnosis and to identify optimal treatments. We report a patient with PRV infection who was admitted to hospital with viral encephalitis and subsequently developed intraocular infection. Because to the lack of relevant clinical experience in the treatment of this disease, we carried out experimental treatment with good therapeutic effect. This case provides a basis for clinical diagnosis and treatment of patients with PRV.